2017
DOI: 10.15226/2374-815x/4/4/00194
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Carbon Dioxide and Air Insufflation in Colonoscopy: A Systematic Review and Meta-Analysis Based On Randomized Control Trials

Abstract: Situs inversus totalis is an extremely rare autosomal recessive disorder occurring in 0.01% of the population. The reversal of visceral organs poses technical difficulties for therapeutic intervention during endoscopic retrograde cholangiopancreatography (ERCP). We describe a unique case of a patient with situs inversus who underwent therapeutic ERCP for management of choledocholithiasis. Case StudyA 37-year-old woman with a history of situs inversus totalis, complex congenital cyanotic heart disease, polysple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…These results are similar to those of several previous meta-analyses analyzing CO 2 and air insufflation use in endoscopic procedures in adult patients. 13,31,33,34 Despite this evidence, variable results have been found in pediatrics. In a pediatric study by Dharmaj et al 2020, 25 multivariate analyses adjusted for baseline pain in children showed that CO 2 insufflation only improved post-procedure pain in those patients with a history of abdominal pain, previous abdominal surgery, and procedures longer than 30 minutes.…”
mentioning
confidence: 99%
“…These results are similar to those of several previous meta-analyses analyzing CO 2 and air insufflation use in endoscopic procedures in adult patients. 13,31,33,34 Despite this evidence, variable results have been found in pediatrics. In a pediatric study by Dharmaj et al 2020, 25 multivariate analyses adjusted for baseline pain in children showed that CO 2 insufflation only improved post-procedure pain in those patients with a history of abdominal pain, previous abdominal surgery, and procedures longer than 30 minutes.…”
mentioning
confidence: 99%